Pengalaman Orang Tua dalam Merawat Anak Berkebutuhan Khusus : Literature Review - Adisty Archi Artamevia Putri; Badrul Munif; Fransiska Erna D; Aulia Amalia; Ayu Ratna Ningrum; Arum Fatmawati; Ajeng Sri Rejeki; Clarisa Artiga Wardani; Awaliah Tri W; Derisca Tiara Patricia; Al Waridlatul Na'imah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2021)
Introduction: The presence of a child in the family is certainly very encouraging for parents. However, it is different from parents who have children with special needs. Children with special needs need different treatment from other children. This of course raises different experiences for each parent in their care. Objective: This study was to determine the psychosocial experience of parents in caring for children with special needs. Method: The method used in this paper is a literature review. With library sources, namely journal articles published in the 2020-2021 period which are full text. Search for journal articles using the Google Schoolar database with the keyword experience; parent; nurse; the child with special needs. Results: This study found 1,500 journal articles which the researchers then took according to the specified criteria, obtained as many as 10 articles. 10 articles reviewed by researchers found 3 journal articles on experiences of parents who can accept the condition of children with special needs and 7 articles found experiences of parents who have psychosocial problems in caring for children with special needs. Conclusion: This literature review found that the experience of parents in caring for children with special needs is divided into two where there are parents who can accept their child's condition sincerely and parents who experience psychosocial problems in the care of children with special needs such as stress, inferiority, shock, rejection, etc. How parents respond to their children with special needs is influenced by many factors such as age, environment, knowledge, etc.